The templar salvation - Khoury, Raymond (Upper St. Martin's Lane, London : Orion Books Ltd., 2011)
To rescue kidnapped Tess Chaykin, FBI agent Sean Reilly infiltrates the Pope's massive Vatican Secret Archives of the Inquisition in search of a document known as the Fondo Templari, a secret history of the infamous Templars.
Keywords: Templars -- History -- Fiction